Culturally Sensitive Counselling in Nunavut: Implications of Inuit Traditional Knowledge - Wihak, Christine; Merali, Noorfarah (Canadian Journal of Counselling and Psychotherapy, 2007)
The success of the Inuit people of Canada in seeking political autonomy resulted in the creation of the Nunavut territory. The new Government of Nunavut (GN) has instituted Inuit Quajimajatiqangit (IQ), the values, norms, and traditional knowledge of the Inuit, as formal policy to guide the delivery of health, social, and civil services in order to ensure their cultural sensitivity. This paper discusses four Inuit IQ principles adopted by the GN that directly relate to the counselling process: Pilimmaksarniq (the importance of felt or revealed truth), Pijitsirniq (community orientation), Inuuqatigiitiarniq (respect and non-interference), and Aajiiqatigiingniq (inclusive decision-making). The paper also describes how non-Aboriginal counsellors working in the Nunavut context can apply these principles in their professional practice with Inuit clients.